Emerging Sponge Models of Animal-Microbe Symbioses - Pita, Lucia; Fraune, Sebastian; Hentschel, Ute (Frontiers in Microbiology, 2016)
Sponges have a significant impact on marine benthic communities, they are of biotechnological interest owing to their production of bioactive natural compounds, and they promise to provide insights into conserved mechanisms of host-microbe interactions in basal metazoans. The natural variability of sponge-microbe associations across species and environments provides a meaningful ecological and evolutionary framework to investigate animal-microbial symbiosis through experimentation in the field and also in aquaria. In addition, next-generation sequencing technologies have shed light on the genomic repertoire of the sponge host and revealed metabolic capacities and symbiotic lifestyle features of their microbiota. However, our understanding of symbiotic mechanisms is still in its infancy. Here, we discuss the potential and limitations of the sponge-microbe symbiosis as emerging models for animal-associated microbiota.